Ligilactobacillus salivarius regulating translocation of core bacteria to enrich mouse intrinsic microbiota of heart and liver in defense of heat stress - Yang, Jiajun; Shang, Peng; Liu, Zongliang; Wang, Jing; Zhang, Bo; Zhang, Hao (Frontiers in Immunology, 2025)
The aim of this study was to elucidate the intrinsic microbiota residing in the heart and liver, which was enriched with Ligilactobacillus salivarius supplementation and its roles in defending anti-oxidation of heat stress. The specific pathogen free (SPF) mice were employed to perform the study. Genomic sequencing showed that the intrinsic microbes in the heart and liver of SPF mice, which were primarily of the genera Burkholderia and Ralstonia, functioned in organic metabolism, environmental information processing, cellular processes, and genetic information processing. Lactobacillus sp. were found in the liver but not in the heart. The heart had a lower bacterial abundance than the liver. A culturomic assay of the heart flushing liquid indicated that the dominant species of bacteria were Ralstonia pickettii, Ralstonia sp._3PA37C10, Ralstonia insidiosa, Burkholderia lata, unclassified _g_ Ralstonia, and unclassified _p_ Pseudomonadota. Intrinsic bacteria exist in the heart due to their inhibitory action against pathogenic Escherichia coli. After, the mice were supplemented with Ligilactobacillus salivarius to optimize the microbiota levels. The dominant bacterial phyla in the liver and heart were Bacillota, Bacteroidota, Pseudomonadota, Thermodesulfobacteriota, andActinomycetota, which comprised 98.2% of total bacteria. The genus Lactobacillus was also abundant. Core bacteria such as Lactobacillus reuteri are translocated from the intestine to the heart and liver. The enriched bacterial composition up-regulated anti-oxidation capacities in the heart and liver. The levels of reactive oxygen species and superoxide dismutase (SOD) were significantly improved compared to those in control (P < 0.01). In conclusion, intrinsic bacteria present in the heart and liver alleviate infection by pathogens, environmental and genetic information processing, and cellular processes during heat stress exposure. Diet with Ligilactobacillus salivarius supplementation regulated the translocation of core bacteria to the heart and liver, improved bacterial composition, and induced a higher anti-oxidative capacity under heat stress.